Summary of discussion - McKeever, Declan J.; Sileghem, M.R.; Gardiner, Peter R.; Gaidulis, L. (International Laboratory for Research on Animal Diseases, 1995)
ILRAD outlined two different areas of research concern to the trypanosomiasis program. One goal was to identify trypanosomal antigens responsible for the immunopathogenesis of the disease by determining how the infection of cattle with trypanosomes affects their immune system. A second goal was to identify protective immune responses that might be targeted at the parasite itself or at the mechanisms through which it causes disease.